Instrumen Penelitian Pendidikan - Nurwahdini Hutasuhut; Meyniar Albina (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Research instruments are essential components in educational research as they function to collect valid and reliable data. However, many studies still use instruments carelessly without proper testing. This study aims to examine the design and development of educational research instruments that comply with scientific standards. The method used is library research by collecting and analyzing written sources such as books, scientific articles, and other relevant documents. The findings indicate that instrument development must follow systematic stages, including variable analysis, blueprint design, item formulation, validity and reliability testing, and final revision. The instruments discussed include both test and non-test types with various data collection techniques. The implication is that this study provides methodological guidance for researchers in designing appropriate instruments to enhance the quality of educational data and research outcomes.